Hayy ibn Yaqzhan: Paradigma Integrasi Filsafat, Pendidikan, dan Islam dalam Menjawab Dikotomi Sains-Agama - Henny Rahma Maulidina; Ikrimah Manjilah Auliya; Nailatuz Zamrudiah; M. Yunus Abu Bakar (JOURNAL SAINS STUDENT RESEARCH, 2026)
The discourse on the essence of self and the cosmos represents a fundamental inquiry in intellectual history. In his allegorical masterpiece, Hayy ibn Yaqzhan, Ibn Tufail presents an autodidact’s epistemological journey toward truth achieved through rational inquiry, empirical investigation, and spiritual intuition—all ultimately converging with divine revelation. This comprehensive study examines the synergistic interconnection between philosophy (encompassing ontology, epistemology, and axiology), education, and Islam as manifested in the narrative, employing the framework of integrative epistemology that explores the intersections of aqidah, philosophy, and balaghah. Employing a qualitative descriptive-analytical methodology through extensive literature review, this research establishes philosophy as the foundational framework, education as the transformative mechanism, and Islam as the ultimate truth that shapes the comprehension of reality and human nature. The analysis demonstrates that the narrative transcends mere philosophical allegory; it offers a holistic educational paradigm particularly relevant for resolving the contemporary dichotomy between religious and scientific knowledge and addressing the spiritual crisis in modern education. The study concludes that Hayy’s journey offers a holistic paradigm crucial for resolving the contemporary science-religion dichotomy in modern education. Furthermore, this investigation explores the narrative’s dialectical tensions, its implications for curriculum design, and its significance in confronting secularization and knowledge fragmentation in contemporary Islamic education.